(untitled) (Research, Society and Development, 2021)
The present work makes observations related to deaths from external causes in the Metropolitan Region of Manaus (RMM). Specifically, it looks at this issue with a focus on accidental drownings and submersions and assaults. The period covered is from 1996 to 2019, with data extracted from the Mortality Information System (SIM/Datasus). The results show that the geographic peculiarities of the state of Amazonas contribute to the drowning rates in these cities and that there is a need to work on educational public policies aimed at caring for the activities carried out on and through water. Otherwise, it also shows that aggressions are one of the causes of death that rises in the studied timeline, which shows that this is an anomaly that affects a significant portion of society.